Can physiological stress alter population persistence? A model with conservation implications. - Romero, L. Michael.; Fefferman, Nina H. (Tufts University. Tisch Library., 2016)
Recent research has focused on the role of physiological stress in species conservation and population persistence. However, it is currently unknown how much stress individuals can withstand before negative impacts on population size will be detectable. In order to generate testable predictions to address this lack, we created a set of theoretical models that incorporate current theories of how stress, and specifically allostasis (cumulative increase in the cost of coping with stressors), alters an individual's ability to survive and reproduce. Surprisingly, our models predicted the following three non-intuitive results: first, populations where the average individual was exposed to high levels of stress relied preferentially on the oldest and most physically fit individuals for reproduction and population persistence; second, this reliance on the most physically fit individuals led to the average physical condition being highest in the populations where the average individual experienced the most stress; and third, any transient perturbation in the amount of average stress exposure led to a decrease in population size. The mechanism responsible for this decrease was dependent upon the direction of the perturbation; an increase in average stress exposure directly resulted in fewer reproducing individuals, whereas a decrease in average stress exposure indirectly decreased population size via density-dependent feedback. These results have important conservation implications. They suggest that the average physical condition of individuals in a population may be a poor measure of how much stress the population is experiencing, that any disturbance which affects the oldest and most physically fit individuals could have a disproportionate effect on the population, and that any change in the amount of stress experienced by the average individual is likely to have a short-term detrimental impact on the population size.